Surveillance cultures following a regional outbreak of carbapenem-resistant Acinetobacter baumannii. (14th April 2022) - Rivera, Frida; Reeme, Allison; Graham, Mary Beth; Buchan, Blake W.; Ledeboer, Nathan A.; Valley, Ann M.; Munoz-Price, L. Silvia
Abstract: Objectives: The primary aim of this study was to assess the epidemiology of carbapenem-resistant Acinetobacter baumannii (CRAB) for 9 months following a regional outbreak with this organism. We also aimed to determine the differential positivity rate from different body sites and characterize the longitudinal changes of surveillance test results among CRAB patients. Design: Observational study. Setting: A 607-bed tertiary-care teaching hospital in Milwaukee, Wisconsin. Patients: Any patient admitted from postacute care facilities and any patient housed in the same inpatient unit as a positive CRAB patient. Methods: Participants underwent CRAB surveillance cultures from tracheostomy secretions, skin, and stool from December 5, 2018, to September 6, 2019. Cultures were performed using a validated, qualitative culture method, and final bacterial identification was performed using mass spectrometry. Results: In total, 682 patients were tested for CRAB, of whom 16 (2.3%) were positive. Of the 16 CRAB-positive patients, 14 (87.5%) were residents from postacute care facilities and 11 (68.8%) were African American. Among positive patients, the positivity rates by body site were 38% (6 of 16) for tracheal aspirations, 56% (9 of 16) for skin, and 82% (13 of 16) for stool. Conclusions: Residents from postacute care facilities were more frequently colonized by CRAB than patients admitted from home. Stool had the highest yield for identification of CRAB.